Migrating production monolithic systems to microservices using aspect oriented programming. (2nd March 2021) - Freire, Augusto Flávio A. A.; Sampaio, Américo Falcone; Carvalho, Luis Heustakio L.; Medeiros, Otávio; Mendonça, Nabor C.
Abstract: Several organizations need to address the challenge to migrate current traditional monolithic applications in production to microservices, preferably, without having to schedule maintenances to take the application offline. This article presents an approach for migrating to microservices with almost zero downtime and minimal changes in the monolithic code. The approach is based on the concepts of aspect‐oriented programming (AOP) and reflection to enable to intercept calls inside the monolith and transform them into service requests invoking the newly built microservices using the concept of around advices. The aspects do the "dirty work" of decoupling what will be refactored and which service to call and practically "zero" code changes need to be done in the original monolithic code. This enables one key novel contribution of our migration approach which is the ability to revert code and data changes without having to take the system offline. Two applications are used as proofs of concept to demonstrate that the proposed approach enables to go "forward" or "backward" among different versions of the application with minimal code or data changes. An evaluation performed in the cloud demonstrates that this work does not introduce significant performance or cost overhead when compared to the current state of the art and to the original monolith.